A Note on the Infinite Sum of the Lerch function (European Journal of Pure and Applied Mathematics, 2022)
We derive the infinite sum of the Lerch function in terms of the incomplete gamma function and the Lerch function. Special cases are evaluated in terms of fundamentals constants. All the results in this work are new.
Keywords: Lerch function; incomplete gamma function; Catalan's constant; Aprey's constant